The Nelson Monument, Barbados - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
View of the historical Nelson Monument, Barbados. There are two partially seen women in foreground and one woman in full view. All three appear to be fully dressed in the fashion of the day. Other male figures can be seen engaging in other activities. Rigging from shipping boats and what seems to be a crane are also visible. Horse and carriages are also seen near the crane. Men pulling wagons of barrels are seen on the right-hand side of the monument. At the back: (ct) At the bottom has written in pencil: €8 and printed in red ink is: 08 69672.
Landscape, coloured, 5 1/2 x 3 1/2 inches.
Keywords: Historical markers; Cities and towns; Monuments and memorials; Clothing and dress; Transportation; City and town life; Transportation; People; Nelson Monument